Community participation in the Integrated Development Planning processes as a means of improving local governance : a case of Polokwane Municipality - Mehlape, Magogodi Mary (My University, 2022)
The study presents findings that examined the nature and extent of community participation in the Integrated Development Planning (IDP) processes as a means of improving local governance at the Polokwane Local Municipality. The study argues for a need to empower communities with knowledge on the available mechanism as a way of fulfilling the dream of a culture of participation. This is to increase unified perception about the value of community participation in improving local governance. However, local governance accountability can be gauged by the extent to which they practise community participation in decision-making in facing up to the challenges of the day. This is done by putting or encouraging community participation in the processes that would help face up to the challenges of the day, including the IDP processes. The study applied a mixed-methods design and a combination of thematic data analysis and Microsoft Excel (spreadsheet) to analyse data gathered. Structured questionnaires were distributed to respective community members in the selected communities: two villages of Potse and Mahlohlokwe; two townships Mankweng Unit D and Mankweng Zone 1; two suburbs - Flora Park and Ivy Park. Furthermore, faceto- face interviews were conducted with the Polokwane municipal officials responsible for IDP, municipal manager, IDP manager and councillors of selected communities. Findings of the study showed that community participation in the IDP processes was viewed as one of the ways of enabling interaction between local government and citizens. However, citizens faced challenges in the process of community participation and that impacted on the level of community participation. It should, therefore, be borne in mind that to improve local governance, it is necessary to look at the extent to which communities are engaged in the processes of improving local governance. Participation of communities in the development planning of their communities can thus help improve local governance. Therefore, community participation should be widely applied in the local government field to enable good governance and sustainable development.
Thesis (MPAM.) -- University of Limpopo, 2022
Keywords: Integrated Development Planning; Improvement of local governance; Polokwane Local Municipality; Social participation; Social development; Rural development -- South Africa -- Limpopo; Social participation -- South Africa -- Limpopo; Community development, Urban -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo